Sliding Window Rough measurable function on $I-$ core of triple sequences of Bernstein operator - Deepmala Rai; N. Subramanian (Journal of the Indonesian Mathematical Society, 2019)
We introduce sliding window rough $I-$ core and study some basic properties of Bernstein polynomials of rough $I-$ convergent of triple sequence spaces and also study the set of all Bernstein polynomials of sliding window of rough $I-$ limits of a triple sequence spaces and relation between analytic ness and Bernstein polynomials of sliding window of rough $I-$ core of a triple sequence spaces.